2021
DOI: 10.2478/kbo-2021-0082
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Simulation as a Service – an Emergent Concept that Supports the Military Education and Training Process Continuity

Abstract: In the last years, the NATO Modelling and Simulation Group (NMSG) has started to develop and put into practice an emergent concept named “Modelling and Simulation as a Service” (MSaaS) with the purpose to provide a permanent service and cloud-based modelling and simulation (M&S) ecosystem to be used by NATO and partner nations. The new M&S ecosystem will help to project and expand the ways of using M&S capabilities for achieving interoperability between participating simulation systems and ensuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The findings showed that digital tools implemented within military engineering training vary depending on the purpose of their use. The literature review revealed that digital tools used in military engineering training include communication tools (Miron & Gherman, 2022;Porancea-Răulea et al, 2023;Ramesh, 2023); content creation tools (Banday et al, 2014;Chen et al, 2019;Udeozor et al, 2023); LMS (Bradley, 2021;Vakaliuk, 2021); collaboration tools (Ramesh, 2023;Udeozor et al, 2023); assessment tools (Farzana, 2023;Porancea-Răulea et al, 2023); simulation and modelling tools (Chen, 2021;Coman et al, 2021); and adaptive learning tools (Barto & Daly, 2021;Duzhyi & Derkach, 2024). Considerable research work was paid towards the analysis of the effectiveness of digital tools (Chen et al, 2019;Spridzāns, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The findings showed that digital tools implemented within military engineering training vary depending on the purpose of their use. The literature review revealed that digital tools used in military engineering training include communication tools (Miron & Gherman, 2022;Porancea-Răulea et al, 2023;Ramesh, 2023); content creation tools (Banday et al, 2014;Chen et al, 2019;Udeozor et al, 2023); LMS (Bradley, 2021;Vakaliuk, 2021); collaboration tools (Ramesh, 2023;Udeozor et al, 2023); assessment tools (Farzana, 2023;Porancea-Răulea et al, 2023); simulation and modelling tools (Chen, 2021;Coman et al, 2021); and adaptive learning tools (Barto & Daly, 2021;Duzhyi & Derkach, 2024). Considerable research work was paid towards the analysis of the effectiveness of digital tools (Chen et al, 2019;Spridzāns, 2023).…”
Section: Discussionmentioning
confidence: 99%